Hubungan antara Kecanduan Media Sosial dengan Kecemasan pada Siswa SMA Negeri 4 Denpasar - Kadek Agus Wirya Sanjaya Putra; Putu Asih Primatanti; Dewa Ayu Agung Alit Suka Astini (Aesculapius Medical Journal, 2024)
[The Relationship between Social Media Addiction and Anxiety of SMA Negeri 4 Denpasar] As technology and information develop, humans cannot be separated from social media. Currently, social media addiction is something experienced by teenagers, they are willing to spend their time which can have a negative impact on psychological conditions, one of which is anxiety. There are many health problems experienced by adolescents, one of which is anxiety. This study aims to determine the relationship between social media addiction and anxiety in students of SMA Negeri 4 Denpasar. This study used an analytic observational method with a cross-sectional approach. The study was conducted at SMA Negeri 4 Denpasar with the study population including all students totaling 1466 students and responded by 258 students. Data collection was conducted using the Social Media Addiction questionnaire adapted from the Internet Addiction Test (IAT) and the Hamilton Anxiety Rating Scale (HARS) questionnaire. Furthermore, the data will be analyzed bivariate using the IBM application SPSS25 and with the Spearman test method. The analysis result is said to be significant if the p-value <0.05. The results showed that most respondents did not experience anxiety (62%). In level of social media addiction are mostly at a moderate level (65.1%). The value Spearman test obtained is 0.388 which indicates the strength of the correlation is low and unidirectional. This means that there is a relationship between social media addiction and anxiety in students of SMA Negeri 4 Denpasar.